Learning Principles Reflected In English Teaching Learning Process At Model Class A Naturalistic Study at SMP N 1 Bodeh Pemalang in Academic Year 2014-2015 - Hibatullah, Achmad; , Prof.Dr.Endang Fauziati (2017)
Achmad Hibatullah, S 200130037: "Learning Principles Reflected in English Teaching Learning Process at Model Class: A Naturalistic Study at SMP N 1 Bodeh Pemalang in Academic Year 2014-2015." This study aimed at analyzing learning principles reflected in English teaching learning process at Model Class of SMP N 1 Bodeh Pemalang. The objectives are to describe types of learning principles, to find out the frequency of each type, and the most dominant learning principle. This is a qualitative research using naturalistic approach. The sources of data are teaching learning activities, respondents, and documents. The data were collected through non-participant observation, interview, and documentation. Data validity was checked using triangulation technique. The data analysis was carried out through procedure of data collection, data reduction, data display, and conclusion. The result showed that there are four learning principles namely behaviorism, cognitivism, humanism, and constructivism reflected during English teaching learning process. The frequency of behaviorism principles is 39, 74%, the frequency of cognitivist principles is 19, 23%, the frequency of humanistic principles is 25, 64%, and the frequency of constructivist principles is 15, 39%. Behaviorism principles is the most dominant learning principles reflected in English teaching learning process at Model Class of SMP N 1 Bodeh Pemalang. Keywords: Learning Principle, Teaching Learning Process, Naturalistic Approach.